MODEL PENGEMBANGAN DESA KARANG BAJO SEBAGAI DESA WISATA ARSITEKTUR TRADISIONAL DI KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Liza Hani Saroya Wardi; Baiq Harly Wijayanti; Agus Kurniawan; Tjatur Kukuh (Bajang Institute, 2023)
The purpose of this research is to find a concept model for the development of a traditional tourism village that is in accordance with the character of the traditional village of Karang Bajo which is thick with its customs and is wise in managing the natural resources that exist in the village of Karang Bajo. In addition, other potential can be seen in local wisdom which contains the values ​​of life that are still alive in the people who live in traditional traditional houses with grid iron settlement patterns. In addition, based on the RTRW of KLU Regency, if KLU becomes a tourism area, it includes the village of Karang Bajo itself.